2016
DOI: 10.1007/s11845-016-1453-3
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated orthogeriatric service reduces hip fracture mortality

Abstract: A multidisciplinary management approach to fragility fracture of the femoral neck that involves comprehensive geriatric assessment, daily medical involvement of a geriatric team and specialised follow-up assessment leads to a significant reduction in mortality and improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…In this review, only one of the six studied hospitals had a geriatrician who routinely assessed hip fracture patients pre-and post- operatively, indicating a lack of geri-orthopaedic co-management in HK. Studies have shown better outcomes after hip fracture when patients receive geri-orthopaedic treatment, with a lower 1-year mortality rate, 26,27 reduced acute hospital stay, and less need for further rehabilitation. 27 A local study reviewed the effectiveness of geri-orthopaedic comanagement and found that in the geri-orthopaedic group, time to surgery was shorter, 1-year mortality rate was lower, and more remained independent in daily living activities.…”
Section: Importance Of Geri-orthopaedic Co-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, only one of the six studied hospitals had a geriatrician who routinely assessed hip fracture patients pre-and post- operatively, indicating a lack of geri-orthopaedic co-management in HK. Studies have shown better outcomes after hip fracture when patients receive geri-orthopaedic treatment, with a lower 1-year mortality rate, 26,27 reduced acute hospital stay, and less need for further rehabilitation. 27 A local study reviewed the effectiveness of geri-orthopaedic comanagement and found that in the geri-orthopaedic group, time to surgery was shorter, 1-year mortality rate was lower, and more remained independent in daily living activities.…”
Section: Importance Of Geri-orthopaedic Co-managementmentioning
confidence: 99%
“…Studies have shown better outcomes after hip fracture when patients receive geri-orthopaedic treatment, with a lower 1-year mortality rate, 26,27 reduced acute hospital stay, and less need for further rehabilitation. 27 A local study reviewed the effectiveness of geri-orthopaedic comanagement and found that in the geri-orthopaedic group, time to surgery was shorter, 1-year mortality rate was lower, and more remained independent in daily living activities. 28 Therefore, geri-orthopaedic care should be implemented in all hospitals in HK to achieve better patient care.…”
Section: Importance Of Geri-orthopaedic Co-managementmentioning
confidence: 99%
“…Other qualitative factors may have also contributed to the low incidence in our cohort. In the geriatrician‐led orthogeriatric team, patients were medically optimised on admission to minimise delay to surgery and post‐operative complications . There was dedicated dietician input for intensive nutritional support post‐operatively in the form of oral nutritional supplement drinks and enteral feeding where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In the geriatrician-led orthogeriatric team, patients were medically optimised on admission to minimise delay to surgery and post-operative complications. [13][14][15][16] There was dedicated dietician input for intensive nutritional support post-operatively in the form of oral nutritional supplement drinks and enteral feeding where appropriate. In critical care patients and burns patients, enteral feeding has been shown as an effective strategy for gastrointestinal stress ulceration prevention and lowers the incidence of UGIB.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…People with dementia have a higher risk of hip fractures and poorer outcomes after fracture, compared with people who are cognitively intact [4]. An Irish study found that 24% of all patients with hip fracture had co-existent dementia [5].…”
Section: Introductionmentioning
confidence: 99%